1998
DOI: 10.1128/aac.42.5.1093
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Concentrations of Sulbactam-Ampicillin Administered by Bolus Injections or Bolus plus Continuous Infusion in Tissues of Patients Undergoing Colorectal Surgery

Abstract: The concentrations of sulbactam and ampicillin were determined in sera and different abdominal tissues of 16 patients who underwent elective colorectal surgery. Patients were randomly allocated to two groups. At the time of induction of anesthesia, patients in group 1 (eight patients) were given 1,000 mg of sulbactam with 2,000 mg of ampicillin by intravenous bolus injection (3 min). This dose was administered again after 2 h by bolus injection by the same route. Patients in group 2 (eight patients) were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Data on tissue concentrations after continuous versus bolus application have been sparse to date 28 . However, most infections take place in the extravascular interstitial space, and serum concentrations or serum bactericidal levels are of limited relevance to the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Data on tissue concentrations after continuous versus bolus application have been sparse to date 28 . However, most infections take place in the extravascular interstitial space, and serum concentrations or serum bactericidal levels are of limited relevance to the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…27 Although a study in 16 patients undergoing colorectal surgery reported IV push administration of 2 g/1 g ampicillin/ sulbactam over 3 minutes, the concentration of the solution was not reported. 121 Similarly to ampicillin, seizures may occur with rapid administration of ampicillin/sulbactam. 66 Finally, the monobactam aztreonam is indicated for IV push administration after reconstitution of vials.…”
Section: Penicillins and Monobactammentioning
confidence: 99%
“…For this reason, clinical studies to prove this administration regimen efficacious continue. Martin et al compared antibiotic concentrations in blood, abdominal wall fat, epiploic fat, and colonic wall tissue samples following administration by consecutive bolus injections versus a bolus injection followed by continuous intravenous infusion [16]. No difference was found in tissue concentrations between the groups, suggesting that a single intravenous bolus of antimicrobials is the preferred method due to increased ease of administration.…”
Section: Timing and Route Of Delivery Of Intravenous Antimicrobialsmentioning
confidence: 99%